2020
DOI: 10.1159/000508914
|View full text |Cite
|
Sign up to set email alerts
|

Four Years of Observation to Evaluate Autonomy and Quality of Life after Implantation of a High-Add Intraocular Lens in Age-Related Macular Degeneration Patients

Abstract: Visual impairment resulting from advanced dry age-related macular degeneration (AMD) limits the ability to perform activities required for independent living and adversely affects quality of life. We aimed to determine changes in these parameters in patients with AMD-related geographic atrophy who underwent magnifying cataract surgery (MAGS) using a foldable, bifocal high-add intraocular lens (IOL). The high-add IOL (LENTIS ® MAX LS-313 MF 80, Oculentis) was implanted in the better seeing or dominant eye of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Borkenstein and Borkenstein 28 reported a study of 11 Austrian patients with GA who underwent magnifying cataract surgery using a foldable, bifocal high-add intraocular lens (IOL) in the better-seeing eye. When completing a questionnaire listing 10 routine activities (reading, recognizing photos, eating and cooking, operating a telephone, daily hygiene rituals, brushing teeth, cutting nails, operating household appliances, manual work, and use of low-vision aids [eg, magnifying glasses]) at 6 months postsurgery, 10 of 11 patients reported limitations in their ability to complete these activities.…”
Section: Resultsmentioning
confidence: 99%
“…Borkenstein and Borkenstein 28 reported a study of 11 Austrian patients with GA who underwent magnifying cataract surgery using a foldable, bifocal high-add intraocular lens (IOL) in the better-seeing eye. When completing a questionnaire listing 10 routine activities (reading, recognizing photos, eating and cooking, operating a telephone, daily hygiene rituals, brushing teeth, cutting nails, operating household appliances, manual work, and use of low-vision aids [eg, magnifying glasses]) at 6 months postsurgery, 10 of 11 patients reported limitations in their ability to complete these activities.…”
Section: Resultsmentioning
confidence: 99%
“…Cataract surgery with implantation of the LS-313 MF80 performed in one eye with simultaneous intravitreal injection of an anti-vascular endothelial growth factor agent improved CDVA and DCNVA [ 18 ]. In a subsequent study by the same authors, 4-years observational outcomes of 11 patients treated with this implant were reported [ 21 ]. The authors found an increase in CDVA and UNVA in all cases and 10/11 patients reported an improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The authors claimed that this IOL offers safe and durable functional and quality of life benefits. They stated that additional clinical research would be needed to collect more outcome data to determine the clinical value of this implant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…ИОЛ LENTIS® MAX LS-313 MF80 представляет собой модификацию вращательного асимметричного рефракционного бифокального LENTIS® Mplus LS-313 MF 30 (Oculentis, Германия), который включает в себя ближний сегмент на передней поверхности, но также и эквивалентный ближний сегмент на задней стороне, чтобы обеспечить прибавку +8,0 D (+6,0 D в очковой плоскости). Бифокальные свойства LENTIS® MAX LS-313 MF 80 обеспечивают хорошее зрение вдаль и увеличение примерно в 2,5 раза вблизи, что может свести к минимуму необходимость увеличения ближнего поля для пациентов с развитой ВМД [38]. В литературе данные о клинической эффективности и безопасности LENTIS® MAX LS-313 MF 80 являются единичными.…”
unclassified